1978
DOI: 10.1111/j.1365-2559.1978.tb01736.x
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic arterial calcification in infancy

Abstract: Three fatal cases of idiopathic arterial calcification in infancy are reported. The infants' ages ranged from 9 days to 3 months. Death was due to cardiac failure; in two cases caused by myocardial ischaemia, and in one by pulmonary hypertension. The histological findings are described and aetiology of the condition is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 10 publications
1
24
0
Order By: Relevance
“…Patient history and clinical data were gathered through a standardized questionnaire, which was sent to the referring physician or geneticist. Diagnosis of GACI was based on the presence of cardiovascular symptoms associated with evidence of arterial calcification with or without periarticular calcification on x-ray or sonography in infancy,1 or typical histology20 (Figure 1). Diagnosis of GACI is exemplified in the following case report: The male infant (case 6 of our study) was born to consanguineous Turkish parents.…”
Section: Methodsmentioning
confidence: 99%
“…Patient history and clinical data were gathered through a standardized questionnaire, which was sent to the referring physician or geneticist. Diagnosis of GACI was based on the presence of cardiovascular symptoms associated with evidence of arterial calcification with or without periarticular calcification on x-ray or sonography in infancy,1 or typical histology20 (Figure 1). Diagnosis of GACI is exemplified in the following case report: The male infant (case 6 of our study) was born to consanguineous Turkish parents.…”
Section: Methodsmentioning
confidence: 99%
“…The pathogenesis of GACI is related to reduced NPP1 enzymatic activity leading to low extracellular PP i levels. [1315]…”
Section: Discussionmentioning
confidence: 99%
“…Calcification may also occur in areas devoid of intimal thickening [Morton, 1978]. Exceptional case reports have indicated that calcification identified in earlier life is not always persistent [Marrott et al, 1984;Sholler et al, 1984;Ciana et al, 2006].…”
Section: Discussionmentioning
confidence: 99%